Beyond right ventricular size and function: the importance of evaluating the right ventricle's capacity for recovery. (November 2014) - Addetia, Karima; Patel, Amit R
<x xml:space="preserve">Abstract</x> Historically, the right ventricle (RV) has received less attention than the left probably because morbidity and mortality associated with left ventricular disease is clinically more apparent. Right heart disease, in contrast, tends to have a more prolonged and, in the early stages, often subclinical course. Furthermore, the left ventricle is easier to image, model and quantify, so that research has been successful at amassing a great deal of clinically useful information about the left heart while the right heart still remains, in many ways, a mystery. In this perspective, the authors sought to explore the topic of RV recovery potential that has important clinical implications in the evaluation and treatment of advanced right-sided valvular heart disease, congenital heart disease, pulmonary arterial disease and even lung disease which impacts the RV. We see a clear need for a better understanding of RV viability given our increasing appreciation that RV failure is a significant contributor to morbidity and mortality in many disease states and the fact that newer imaging modalities and innovative changes to older modalities make more comprehensive evaluation of the RV feasible.